Digital Marketing dengan menggunakan Google Bisnis untuk para Usaha Mikro, Kecil, dan Menengah (UMKM) di Kelurahan Palmerah - Rahmat Rian Hidayat; Dhanny Permatasari Putri; Risma Bayu Putra (PEMANAS: Jurnal Pengabdian Masyarakat Nasional, 2022)
Micro, Small and Medium Enterprises (MSMEs) are businesses engaged in trade, which involves entrepreneurship activities. MSME actors in the Palmerah sub-district registered around 160 MSMEs in 2020 with various business fields that they are interested in. One part of the existing UMKM business, for example in the field of fashion, MUA (makeup artist), Furniture, Decoration, video and photo services, selling books, culinary. This community service is carried out to assist MSMEs in increasing their knowledge and skills about digital marketing, especially tips on how to easily use features on Google for easy verification. The use of Google My Business is a good feature to increase sales, especially the identity of the MSMEs can be easily accessed. This community service was carried out in the Palmerah village by involving MSMEs and lecturers from Mercu Buana University in the Informatics Study Program. In the implementation of this service, it is held online (Zoom meeting). The participants were very enthusiastic, as evidenced by the response which stated that the overall event was very good and the material presented was very useful for MSME industry players. Keywords: MSME, Business, Online